Immunogenicity and safety of an egg-based inactivated quadrivalent influenza vaccine (GC3110A) versus two inactivated trivalent influenza vaccines with alternate B strains: A phase Ⅲ randomized clinical trial in adults. Issue 3 (4th March 2019) - Song, Joon Young; Lee, Jacob; Woo, Heung Jeong; Wie, Seong-Heon; Lee, Jin Soo; Kim, Shin Woo; Kim, Tae Hyong; Jung, Sook-In; Noh, Ji Yun; Choi, Won Suk; Cheong, Hee Jin; Kim, Woo Joo
ABSTRACT: Two antigenically distinct influenza B lineage viruses (Yamagata/Victoria) have been co-circulating globally since the mid-1980s. The quadrivalent influenza vaccine (QIV) may provide better protection against unpredictable B strains. We conducted a randomized, double-blind, phase III trial to evaluate the immunogenicity and safety of an egg-based inactivated, split-virion QIV (GC3110A). Subjects aged ≥ 19 years were randomized 2:1:1 to be vaccinated with QIV- GC3110A, trivalent influenza vaccine (TIV) containing the Yamagata lineage strain (TIV-Yamagata), or TIV containing the Victoria lineage strain (TIV-Victoria). Hemagglutination inhibition assays were performed 21 days post-vaccination. Solicited/unsolicited adverse events (AEs) were assessed within 21 days after vaccination, while serious AEs were reported up to six months after vaccination. A total of 1, 299 were randomized to receive QIV-GC3110A (648 subjects), TIV-Yamagata (325 subjects), or TIV-Victoria (326 subjects). Compared to the TIVs, the QIV-GC3110A met the non-inferiority criteria for all four subtype/lineage strains with respect to the geometric mean titer (GMT) ratio and the difference of seroconversion rate. The safety profiles of QIV-GC3110A were consistent with those of TIV. In conclusion, QIV-GC3110A is safe, immunogenic, and comparable to strain-matched TIV.